NGO credibility as private or public good? A governance perspective on how to improve NGO advocacy in public discourse - Stefan Hielscher; Jan Winkin; Ingo Pies (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2016)
Though research in the field of business and society is increasingly involved with the sector of Non-Governmental Organizations (NGOs) and their advocacy function, in particular in relation to business corporations, the literature remains largely silent on how feasible reforms can help establish public trust in and credibility of NGOs by improving the quality and reliability of their contributions to real-life public discourses. In an effort to fill this gap, we argue that fostering the collective credibility of NGO advocacy requires focusing on the level of governance of NGO accountability. Based on a fundamental conceptual distinction between a private-goods dimension and a public-goods dimension of NGO accountability, we can show that semantic confusion can complicate functional solutions to establish collective NGO credibility and public trust. We illustrate our argument with a case study of a worldwide governance initiative in this sector, the ,,INGO-Accountability Charter“, including qualitative-empirical results on five expert interviews with representatives of NGO member organizations. – – Das Forschungsfeld der Wirtschafts- und Unternehmensethik beschäftigt sich zunehmend mit Nichtregierungsorganisationen (Non-Governmental Organizations, NGOs), mit den Beziehungen zwischen Unternehmen und NGOs sowie mit der gesellschaftlichen Advocacy-Funktion von NGOs als Interessenvertretung marginalisierter Gruppen. Allerdings fehlt es bisher an Ansätzen, wie die kollektive Glaubwürdigkeit des zivilgesellschaftlichen Sektors durch eine qualitative Verbesserung der Diskursbeiträge von NGOs gefördert werden kann. Um diese Lücke zu füllen, entwickeln wir konzeptionelle Reformüberlegungen, die auf der Governance-Ebene ansetzen, um die Glaubwürdigkeit (,,Accountability“) von NGOs zu erhöhen. Basierend auf der Unterscheidung, ob die Glaubwürdigkeit von NGOs den Charakter eines privaten oder eines öffentlichen Gutes aufweist, können wir zeigen, dass eine ,semantische Verwirrung` funktionale Lösungsansätze zur Stärkung der kollektiven Glaubwürdigkeit des zivilgesellschaftlichen Sektors erschwert. Wir verdeutlichen die praktische Relevanz unserer Argumentation an Hand einer Fallstudie der weltweiten Governance-Initiative ,,INGO-Accountability Charter“ und werten hierzu fünf Experteninterviews mit Repräsentanten von Mitgliedsorganisationen aus.
urn:nbn:de:gbv:3:2-54050
Keywords: 330; Business-NGO Relations; NGO Accountability; Public Discourse; Governance; Ordonomics; Business-NGO-Beziehungen; NGO Accountability; Öffentliche Diskurse; Governance; Ordonomik